The qualitative experience of telehealth access and clinical encounters in Australian healthcare during COVID-19: implications for policy - Jennifer White; Julie Byles; Tom Walley (BMC, 2022)
Abstract Background Adaptive models of healthcare delivery, such as telehealth consultations, have rapidly been adopted to ensure ongoing delivery of essential healthcare services during the COVID-19 pandemic. However, there remain gaps in our understanding of how clinicians have adapted to telehealth. This study aims to explore the telehealth experiences of specialists, based at a tertiary hospital in the Hunter Region, and general practitioners (GP), including barriers, enablers and opportunities. Methods An interpretative qualitative study involving in-depth interviews explored the telehealth experiences of specialists, based at a tertiary hospital in the Hunter Region of Australia, and GPs, including barriers, enablers and opportunities. Data were analysed using an inductive thematic approach with constant comparison. Results Individual interviews were conducted with 10 specialists and five GPs. Key themes were identified: (1) transition to telehealth has been valuable but challenging; (2) persisting telehealth process barriers need to be addressed; (3) establishing when face-to-face consults are essential; (4) changes in workload pressures and potential for double-up; (5) essential modification of work practices; and (6) exploring what is needed going forward. Conclusions While there is a need to rationalize and optimize health access during a pandemic, we suggest that more needs to be done to improve telehealth going forward. Our results have important policy implications. Specifically, there is a need to effectively train clinicians to competently utilize and be confident using this telehealth and to educate patients on necessary skills and etiquette.